2019
DOI: 10.2147/ott.s201233
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC00491 as a new molecular marker can promote the proliferation, migration and invasion of colon adenocarcinoma cells</p>

Abstract: Background: Long non-coding RNAs (lncRNAs) play an important role in the pathogenesis of multiple tumors. However, the roles of lncRNAs during colon adenocarcinoma and cancer progression remain unclear. This study aimed identify new lncRNAs that act as molecular markers for the prevention and diagnosis of colon adenocarcinoma. Methods: RNA sequencing (RNA-Seq) data associated with colon adenocarcinoma were retrieved from the Cancer Genome Atlas (TCGA). Biological processes in Gene Ontology (Go) and the Kyoto E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…10 In addition, similar to protein-coding genes, lncRNA has important roles in diverse cellular processes by silencing miRNA, which was a canonical competing endogenous RNA (ceRNA) regulating pattern; moreover, frequent dysregulation of lncRNA already associated with many vital cellular processes and pathogenesis of tumors. 11,12 A study has shown that abnormal expression of lncRNA participated in initiation, progression, metastasis, and drug resistance of human malignancies. 13 For instance, colon cancer-associated transcript-1 (CCAT1) has been defined as an oncogenic lncRNA in glioma and acute myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, similar to protein-coding genes, lncRNA has important roles in diverse cellular processes by silencing miRNA, which was a canonical competing endogenous RNA (ceRNA) regulating pattern; moreover, frequent dysregulation of lncRNA already associated with many vital cellular processes and pathogenesis of tumors. 11,12 A study has shown that abnormal expression of lncRNA participated in initiation, progression, metastasis, and drug resistance of human malignancies. 13 For instance, colon cancer-associated transcript-1 (CCAT1) has been defined as an oncogenic lncRNA in glioma and acute myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained by Nie et al [33], whose expression analysis of miR-365 by qPCR was also decreased in the CRC cell lines, HT29, LoVo, SW480 and SW620, compared with normal colon mucosa tissues. Wan et al [53] also corroborated by PCR that the expression levels of miR-145 were significantly suppressed in the CRC cell lines, HT-29 and HCT116 cells. In order to make the assays with sponges we chose 3 CRC cell lines: the two lines with higher expression of both miRNAs (RKO and T84) and the line with lower expression (HCT116).…”
Section: Discussionmentioning
confidence: 78%
“…ENST00000510145 is one of nine transcripts of gene ENSG00000250682, also known as LINC00491 or BC008363. This gene was found to be upregulated in a TCGA colon adenocarcinoma dataset and was associated with lower patient survival, implying ENSG00000250682 importance for colorectal cancer progression 53 . Conversely, in pancreatic ductal adenocarcinoma patients LINC00491 expression was significantly lower compared to the control group and was associated with better survival rates 54 .…”
Section: Resultsmentioning
confidence: 99%